2012
DOI: 10.1177/0013916512453839
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative and Comprehensive Methodology for Studying Aesthetic Experience in the Field

Abstract: In the interdisciplinary context of the Swiss National Research Project eMotion-mapping museum experience, an integrative methodology for visitor research was developed. The goal was to investigate aesthetic experiences in the environment of a fine-arts museum. The methodology and technical setup merged different data levels (movement tracking data, heart rate and skin conductance, sociological variables, emotional and aesthetic evaluations of specific artworks) into one integrated data set. The merging was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…Finally, characteristics of the presentation context include physical and cultural aspects of the museum, display/hanging, frame, lighting, art labels, furniture, movement, viewing distance, viewing time and museum fatigue. While all of these factors might be contributing to differences between art experience in museum and other contexts, to date, the majority of them have remained underexplored (Bitgood et al, 2013;Minissale, 2013;Tröndle et al, 2014;Carbon, 2017).…”
Section: What Causes Difference In Art Experience and Viewing Patternmentioning
confidence: 99%
“…Finally, characteristics of the presentation context include physical and cultural aspects of the museum, display/hanging, frame, lighting, art labels, furniture, movement, viewing distance, viewing time and museum fatigue. While all of these factors might be contributing to differences between art experience in museum and other contexts, to date, the majority of them have remained underexplored (Bitgood et al, 2013;Minissale, 2013;Tröndle et al, 2014;Carbon, 2017).…”
Section: What Causes Difference In Art Experience and Viewing Patternmentioning
confidence: 99%
“…In 2012, the project "eMotion" was funded by the Swiss National Science Foundation, and data from 576 users was collected by Tröndle during their visit to an exhibition. Measurements included Heart Rate Variability (HRV) and Skin Conductance Levels (SCLs) [22]. Unlike Tröndle, Saarinen allowed users to be involved in the project rather than simply being observed and measured objects [23].…”
Section: Methods Of Studying Exhibition Designmentioning
confidence: 99%
“…More advanced methods have introduced automatic user tracking, partly combined with continuous recording of physiological measures such as skin conductance and heart rate in order to determine intensity of emotional and cognitive reactions across an exhibition (Tr€ ondle, Greenwood, Kirchberg, & Tschacher, 2014). But at least in the case of showcases containing sets of exhibits, traditional observation methods reach their limits, as Study 1 has demonstrated: While visitor tracking is feasible for exhibitions presenting spatially separated objects (such as paintings in an art museum or interactive stations in a science center), it not only lacks sufficient resolution for discrimination between objects that are presented as ensembles in display cabinets, but also does not allow for investigating whether visitors access additional information and explanations, either by reading labels and placards or by using audioguides or mobile guides.…”
Section: Studymentioning
confidence: 99%